Let’s Build a Medieval Tile Kiln - Introducing Experimental Archaeology into the University Curriculum - Gaynor Wood (EXARC Journal)
As a lecturer at the University of Central Lancashire (UCLAN) I teach a course on medieval archaeology and run a successful programme in designing exhibitions for local museums and community groups. I also encourage my students to take part in the community archaeology and history projects that I run with archaeological and historical local groups in Preston. Students are very keen to take practical work, whether it is researching, excavating, designing a website or conducting local oral history projects, and they gain a lot of confidence from these experiences. This article describes reconstructing and firing a 14th century floor tile kin in the grounds of the museum where the original was found. The author discusses the use of the innovative Problem Based Learning pedagogy to inspire the students and asks if is possible to bring experimental archaeology projects into the University curriculum.